Technology for mercury removal from flue gas of coal based thermal power plants: A comprehensive review. Issue 18 (17th September 2019) - Balasundaram, Karthik; Sharma, Mukesh
Abstract: Vapor phase mercury is a toxic gas emitted largely from coal-based thermal power plants (CTPPs). By the year 2020, approximately 477 tonnes/year of mercury is estimated to be released globally from CTPPs. To address this concern, various regulations, international agreements and action plans have been formulated. Thus, there is an emerging need to address the mercury emission issue from CTPPs in an efficient and cost-effective manner. Over the last five years (2012–2017), a number of research papers have demonstrated different technologies for control of mercury emissions from flue gas. There is a need to create a synthesis of a large number of research efforts to provide insight into technologies their applications, limitations and future advancements. Specifically, this review article integrates the technology developments (from the past five years) into a scientific repository which can provide a ready reference for technology application and at the same time outlines the challenges. This review article is expected to spur further research to address the current gaps and develop technologies for the removal of mercury and other pollutants from CTPPs.